2014
DOI: 10.1080/15222055.2014.899531
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Graded Taurine Levels on Juvenile Cobia

Abstract: Taurine, which has multiple important physiological roles in teleost fish and mammals, is an amino acid not found in alternative protein sources not derived from animals. Although taurine is found in fish‐meal‐based feeds, its high water solubility leads to lower taurine levels in reduction‐process‐based feeds, which marine carnivores such as Cobia Rachycentron canadum are adapted to in their natural diets. Graded taurine supplementation (0, 0.5, 1.5, and 5.0%) added to a traditional fish‐meal‐based formulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 41 publications
3
28
0
2
Order By: Relevance
“…The diet without taurine supplementation (M) significantly declined Persian sturgeons' growth performance, which is in accordance with previous studies on different fish species (Chatzifotis et al., ; Han et al., ; Jirsa et al., ; Johnson et al., ; Lim et al., ; Matsunari et al., ; Park, Takeuchi, Yokoyama, & Seikai, ; Watson et al., ; Wu et al., ). Taurine may be synthesized endogenously from methionine, but this capacity depends on fish species (El‐Sayed, ; Salze & Davis, ); nevertheless, it has been suggested that taurine supplementation augments trout growth only when dietary methionine level is suboptimal (Gaylord et al., ), meaning that this species is efficiently able to convert methionine to taurine.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The diet without taurine supplementation (M) significantly declined Persian sturgeons' growth performance, which is in accordance with previous studies on different fish species (Chatzifotis et al., ; Han et al., ; Jirsa et al., ; Johnson et al., ; Lim et al., ; Matsunari et al., ; Park, Takeuchi, Yokoyama, & Seikai, ; Watson et al., ; Wu et al., ). Taurine may be synthesized endogenously from methionine, but this capacity depends on fish species (El‐Sayed, ; Salze & Davis, ); nevertheless, it has been suggested that taurine supplementation augments trout growth only when dietary methionine level is suboptimal (Gaylord et al., ), meaning that this species is efficiently able to convert methionine to taurine.…”
Section: Discussionsupporting
confidence: 88%
“…These results are hard to interpret. Dietary taurine supplementation increased muscle and/or liver taurine content in R. canadum , P. olivaceus and P. major (Han et al., ; Kim et al., ; Matsunari et al., ; Watson et al., ). In S. salar , methionine intake increased muscle and liver taurine, but had no effects on methionine levels (Espe et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A deficiency of taurine in plant-based diets has been linked to the reduced lipid deposition in the tissues of cobia (Lunger, McLean, Gaylord, Kuhn, & Craig, 2007). However, in the current study, taurine was added at 5 g/kg to satisfy the nutritional needs of cobia as quantified by Watson et al (2014). Thus, the reduced muscle lipid contents of cobia fed 315 g/kg LKM diet in the current study might be due to the low energy intake and energy digestibility, similar in cobia fed other plant-derived ingredients (Luo et al, 2012;Luo et al, 2013;Zhou et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Chromic oxide (Cr 2 O 3 ) was added to all test diets as the inner marker. Taurine (Sigma-Aldrich, St. Louis, MO, USA) was added to all diets at a level of 5 g/kg to meet the nutritional requirement of cobia as the recommendation by Watson, Barrows, and Place (2014). Fish oil and distilled water were added and then thoroughly mixed.…”
Section: Experimental Diet Preparationmentioning
confidence: 99%